HUBUNGAN SANITASI DENGAN TOTAL MIKROBA DAN TOTAL KOLIFORM PADA JAMU GENDONG DI RT,1 RW.2 KELURAHAN KEDUNG MUNDU KECAMATAN TEMBALANG KOTA SEMARANG - Nurrahman -; Mifbakhuddin -; Dewi Purnamasari (JURNAL KESEHATAN, 2010)
The sellers ofjamu gendong was need observation in making and ready oftraditional beverage i, ord", not endanger health of society. The observation and inspection necessqry to be done to protect society ofcontagious disease pass beverage they sold. lYith existance of low sanitation can have an ffict on total microbe and total colifurm of jamu gendong. The objective of this research was to know the relation ofsanitatiott with total microbe and total colifurm at jamu gendong in RT. I RW.2 Kedung Mundu Village Tembalang Sub District Semarang City. The type of this research was explanatory research with Crossectional approach and survey of method with inspection at laboratory. Research sampel was total population that was l2 seller and subject of research was jamu gendong for inspection of total microbe and total colform. With I sort of jamu takenfrom each seller thatwas berqs kencur, so that total inspectionsampel was 12 sampel. Independen variable of this research was sanitation, dependen variable were total microbe and total colifurm which implied in jamu gendong. Score value of sanitation on this research between 2l up to 29, with mean 25,50 and standar deviation 2,43. After the categorize ; the sanitation of this research includes of enough c-otegory 000%r). Total microbe of this research between 4,2 x lAi/ml up to 8,8 x 105/ml, with meqn 1,2 x 104/mt standar devition 2,5513 x 1T5/ml, total coliftrm of this between 3 up n 2400 with mean 720,83 and standar deviation 911. Persuant to kolmogorov smirnov test the value of sanitationpvalue : 0,955 and total colifurm p-value : 0,339, meanings sanitation data and total colifurm hqve normat assumption, The value of total mikrobe p-value : 0,019, meanings total microbe data have not normal assumption. Persuant to result of Rank Spearman statistical test value of p equal to 0,002 (<0,05) and result of statistical corelation test of Pearson Produt Moment value of p equal to 0,025 (<0,05). There wassignificant corelation between sanitation with total microbe (r - 0,795) and sanitaion with total colifurm (r - 0,641) atjamu gendong.Keyword : Sanitation, Total Microbe, Total Coliform